VARATIONS IN GLUCOSE, CHOLESTEROL AND PROTEIN LEVEL OF BLOOD SERUM IN RANA TIGRINA IN RELATION TO BODY WEIGHT SEASON AND SEX - SINHA, IRA; MISHRA, V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
In R. tigrina the glucose level increased significantly whereas, the protein level decreased significantly in both the sexes with increasing body weight during summer, rainy and winter season. The cholesterol level showed the significant increasirig trend during summer and significant decreasing trend during rainy season in both the sexes with increasing body weight. During winter season the decreasing trend was insignificant in male whereas, significant in female. The increasing or decreasing trend of glucose, cholesterol and protein content of blood serum were not the same but showing variations with body weight, season and sex,